Transitions in mental health and addiction care for youth and their families: a scoping review of needs, barriers, and facilitators - Roula Markoulakis; Hinaya Cader; Samantha Chan; Sugy Kodeeswaran; Tracey Addison; Cathy Walsh; Amy Cheung; Jocelyn Charles; Deepy Sur; Michael Scarpitti; David Willis; Anthony Levitt (BMC, 2023)
Abstract Introduction Transitional-aged youth (TAY) with mental health and/or addictions (MHA) concerns and their families experience significant challenges finding, accessing, and transitioning through needed MHA care. To develop appropriate supports that assist TAY and their families in navigating MHA care, their experiences of transitions in the MHA care system must be better understood. This scoping review identifies and explores the needs, barriers, and facilitators for TAY and their families when transitioning through MHA care. Methods This scoping review commenced with a search of five relevant databases. Three research team members were involved in title, abstract, and full-text scanning and data extraction. Sources focusing on TAY anywhere between the ages of 12-29 years and meeting the study objectives were included. Extractions compiled background and narrative information about the nature and extent of the data. Analysis and synthesis of findings involved numerical description of the general information extracted (e.g., numbers of sources by country) and thematic analysis of narrative information extracted (e.g., family involvement in TAY help-seeking). Results A total of 5894 sources were identified. Following title and abstract scanning, 1037 sources remained for full-text review. A total of 66 sources were extracted. Findings include background information about extracted sources, in addition to five themes that emerged pertaining to barriers and facilitators to access and transitions through care and the needs and roles of TAY and families in supporting help-seeking and care transitions: holistic supports, proactive preparation, empowering TAY and families, collaborative relationships, and systemic considerations. These five themes demonstrate approaches to care that can ensure TAY and families' needs are met, barriers are mitigated, and facilitators are enhanced. Conclusion This review provides essential contextual information regarding TAY with MHA concerns and their families' needs when seeking care. Such findings lend to an enhanced understanding of how MHA programs can support this population's needs, involve family members as appropriate, reduce the barriers experienced, and work to build upon existing facilitators.